STtTDIElS ON THE MORTALITY IN SPAWN AND FRY OF INDIAN MAJOR CARPS DURING TRANSPORT Part IV. Types of Containers Used for Transporting Spawn and Fry under Oxygen Pressure - Saha, K C; Sen, D P (Indian Journal of Fisheries, 2016)
For transporting the fry of Indian major carps, three types of containers, viz., glass carboy, specially designed aluminium and galvanized iron sheet containers and latex-rubber and plastic bags, have been described. Although from the point of view of efficiency the specially designed aluminium container has been found most suitable, considering the relative costs of different types of containers tried, latex-rubber bag may be recommended for commercial use.